Obesity Class Impacts Adverse Maternal and Neonatal Outcomes Independent of Diabetes - Neal, Kirsten; Ullah, Shahid; Glastras, Sarah J. (Frontiers in Endocrinology, 2022)
Obesity in pregnancy is a known risk factor for adverse maternal and neonatal outcomes. Few studies have compared adverse pregnancy-related outcomes according to obesity severity. Hence, we aimed to examine the impact of obesity class on maternal and perinatal outcomes. Methods: We retrospectively analysed data from all singleton births from mothers with obesity from 2013-2017 in Northern Sydney Local Health District in Sydney, Australia. Women were categorised into obesity class I (BMI 30-34.9kg/m2), class II (BMI 35-39.9 kg/m2) or class III (BMI 40+ kg/m2). Across BMI classes, we compared maternal outcomes including mode of delivery, gestational diabetes mellitus (GDM), and preeclampsia, and neonatal outcomes including large- and small-for-gestational age (SGA, LGA), neonatal hypoglycaemia, birth defects and timing of birth. Logistic analyses were performed to explore the impact of maternal obesity class on these outcomes, adjusting for maternal age, country of birth, parity, diabetes (both pre-existing and gestational) and hypertension. Results: There were 2466 births to women with obesity, class (69.1%), class II (21.8%), and class III (9.2%) . 42.5% delivered by Caesarean section, 22.3% developed GDM and 11.2% had a hypertensive disorder in pregnancy, and Caesarean section and GDM were more common in women with higher class obesity. LGA occurred in 27.3% and SGA occurred in 4.0% of women across all classes of obesity. LGA rates were 49% more likely in women with class III compared to women with class I obesity (OR=1.49, CI 1.06-2.09, p=0.02). The presence of diabetes in the index pregnancy did not significantly impact risk of neonatal LGA between maternal obesity classes. Other neonatal adverse outcomes such as stillbirth and birth defects were more common in women with higher class obesity. SGA, neonatal hypoglycaemia, gestational age at delivery, APGAR 5-minute score and NICU admissions were similar across obesity classes, after adjustment for covariates. Conclusions: Obesity class increases the risk of many adverse maternal and neonatal outcomes. Obesity class is independently associated with LGA incidence in the neonate, independent of maternal factors including GDM. Ongoing efforts must be made to reduce obesity incidence in women of reproductive age to circumvent the adverse perinatal outcomes associated with obesity.